The Potential of Mucor irregularis Isolated From Fruits in Producing Microbial Lipid - Haura, Alya; Ilmi, Miftahul (Malaysian Applied Biology, 2024)
In this present study, potential oleaginous Mucorales fungi that have been isolated from fruits from local markets in Sleman, Indonesia, were screened for lipid production. A total of six fungal cultures were isolated and screened using a semisynthetic medium with glucose as a carbon source and a limited nitrogen supply. The highest lipid content was observed in isolate JR 1.1, up to 43.46% and 3.28 g/L lipid yield. Therefore, it was selected for molecular identification and fatty acid analysis. The result showed that JR 1.1 was identified as Mucor irregularis. The fatty acid profile of JR 1.1 showed 16.89% palmitoleic acid, 4.85% oleic acid, 45.22% linolenic acid, 30.79% gamma-linolenic acid, and 2.25% other fatty acids. It can be concluded that M. irregularis JR 1.1 is a potential strain to be used as a lipid producer for biodiesel feedstock. Further studies are recommended to optimize lipid productivity and improve fatty acid composition.